Unified bench press through the elimination of leg-drive to promote sports inclusion - Tiziana D'Isanto; Francesca D'Elia; Sara Aliberti; Felice Di Domenico; Giovanni Esposito (Physical Education of Students, 2023)
Background and Study Aim. Among the weightlifting disciplines we find the bench press in Powerlifting and Para Powerlifting, which are very similar. They have never been combined for several reasons, the most important of which is the use of two different barbell lifting techniques. Unlike Para Powerlifting, Powerlifting in the bench press involves the use of leg-drive, i.e. leg thrust, which is considered one of the possible determining factors for the success of this exercise. The aim of the study was to test whether the elimination of the leg-drive technique in Powerlifting, followed by a protocol of adapting to the Para Powerlifting technique, without leg-drive, made a difference in terms of lifting the maximum load (1RM).